2014
DOI: 10.1166/jnn.2014.9380
|View full text |Cite
|
Sign up to set email alerts
|

Perylenetetracarboxylic Diimide (PTCDI) Nanowires for Sensing Ethyl Acetate in Wine

Abstract: We report the application of perylenetetracarboxylic diimide (PTCDI) nanowires for sensing ethyl acetate. The conductivity of the crystalline nano/microwires increases quickly and selectively in the presence of ethyl acetate vapor, but not with water, acid and alcohol vapors, suggesting that the nanowires of PTCDI may be used for monitoring ethyl acetate during a wine manufacturing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the extraction of SO 2 from wine samples, the big advantage of HS–TFME is that less substrate disturbance was caused by the sample. According to previous reports, the main coexisting volatile components in wine include ethanol, isopropyl alcohol, ethyl acetate, nerolidol, and acetaldehyde. The interference by these compounds was estimated following the same procedure as the sulfite analysis, except that the Na 2 SO 3 solution was replaced by the different above-mentioned volatile components at a concentration of 1000 μg/mL.…”
Section: Resultsmentioning
confidence: 89%
“…In the extraction of SO 2 from wine samples, the big advantage of HS–TFME is that less substrate disturbance was caused by the sample. According to previous reports, the main coexisting volatile components in wine include ethanol, isopropyl alcohol, ethyl acetate, nerolidol, and acetaldehyde. The interference by these compounds was estimated following the same procedure as the sulfite analysis, except that the Na 2 SO 3 solution was replaced by the different above-mentioned volatile components at a concentration of 1000 μg/mL.…”
Section: Resultsmentioning
confidence: 89%
“…11,32,33 According to previous studies, the coexisting volatile components including ethanol, isopropyl alcohol, ethyl acetate, nerolidol, and acetaldehyde would most likely interfere with the determination of SO 2 . [34][35][36] Coincidently, through the comparison of the reported Raman spectra of these compounds, no obvious SERS signal was observed at the 620 cm −1 shift. Thus, it can be concluded that the coexisting volatile components in wine samples would not interfere with the determination of SO 2 .…”
Section: Reproducibility Of Sers Signal Using the μPadmentioning
confidence: 91%
“…Under a proper set of conditions, similarly as described earlier, this process allows for the formation of nanostructures such as nanofibers or nanobelts. [ 18 ] Several research groups have demonstrated the potential of PVD‐processed nanomaterials in optoelectronic applications [ 19 ] including sensors [ 20 ] and transistors [ 21 ] as well as in biomedical and health care applications. [ 22 ] Molecular building blocks, which were used for this purpose, are among others pentacene, perylene, and porphyrin derivatives.…”
Section: Introductionmentioning
confidence: 99%